Pembuatan Website UMKM Ampera Evi Menggunakkan Blogger Untuk Pengembangan Pemasaran Dan Promosi - Dio aguswantoro; Azya Maharani Oktaputri; Suci rahmawati; Sularno (CV. ITTC INDONESIA, 2024)
Ampera Evi is a business that sells home-cooked food with a variety of food menus or dishes to choose from. Ampera is located at Jl. Perintis Independen NO 38, West Sumatra, Padang City, East Padang District. Food with various types of food, for example such as bamboo shoot curry, samba lado tanak, kalio beef. The author conducted interviews and documentation and created a website aimed at increasing the sales appeal of Ampera Evi. Apart from that, through the website the information that has been created is provided in detail, complete, and can provide a more attractive appearance. . The method used in collecting data is a qualitative method by conducting interviews and documentation. The author visited and made direct observations at Ampera Evi to obtain various things needed regarding the design. This design produces the main media in the form of the Ampera Evi Information Media Website.